Parent and Physician Global Assessment Discordance in Juvenile Arthritis: The Role of Pain Coping Strategies - Backström, Maria; Halttu, Anna; Tarkiainen, Maarit; Lehtinen, Ella; Sard, Sirja; Keskitalo, Paula; Markula-Patjas, Kati; Rebane, Katariina; Aalto, Kristiina; Remes-Pakarinen, Terhi; Kärki, Johanna; Hietanen, Maiju; et al. (Elsevier BV, 2026)
Objective
To evaluate the factors underlying the discordance in physicians', patients', and caregivers' perceptions of disease state in patients with juvenile idiopathic arthritis and their caregivers in a prospective observational study.
Study design
We invited all children in 8 centers in Finland from November 2021 to March 2024 presenting with newly confirmed or suspected juvenile idiopathic arthritis and the accompanying parents to participate. Children older than 8.0 years and all the parents completed the patient and parent proxy pain and global assessment of wellbeing at 0 and 3 months and the pain coping scale at 3 months after diagnosis. The discordance between patient or parent global assessment and physician global assessment of disease activity was determined by subtracting the physician global from the patient or parent global assessment. The factors explaining discordance between the global assessments, were evaluated by a multivariable linear model.
Results
In the study, 186 families participated. A positive or negative discordance of 30 mm or greater was seen in 17% of the children and 11% of the caregivers. In the children, the lower the active joint count (AJC) (P = .006) and the greater the pain assessment (P < .001), the greater the discordance between patient and physician global assessment. In parents, the lower the AJC (P < .001) and the higher the parent proxy pain assessment (P < .001) and catastrophizing score (P < .005), the greater the discordance between parent and physician global assessment.
Conclusion
The discordance between parent's and physician's global assessment is greater among parents who use catastrophizing as a pain coping strategy.